2017
DOI: 10.1016/j.jaci.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections in allergy and immunology: How allergic inflammation influences viral infections and illness

Abstract: Viral respiratory tract infections are associated with asthma inception in early life and asthma exacerbations in older children and adults. Although how viruses influence asthma inception is poorly understood, much research has focused on the host response to respiratory viruses and how viruses can promote; or how the host response is affected by subsequent allergen sensitization and exposure. This review focuses on the innate interferon-mediated host response to respiratory viruses and discusses and summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(183 citation statements)
references
References 97 publications
(176 reference statements)
5
172
2
4
Order By: Relevance
“…This suggested that the obverse may be true: that adequate control of asthma exacerbations could reduce the incidence of diagnosis of respiratory tract infections, as was reported in a previous study (Pelaia et al, ). The underlying mechanism might be due to un‐disrupted interferon production in children with adequate asthma control compared with decreased interferon production in those with poor asthma control (Edwards et al, ; Sykes et al, ). Interferon is a major cytokine that regulates lung inflammation and protects lungs from infections.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the obverse may be true: that adequate control of asthma exacerbations could reduce the incidence of diagnosis of respiratory tract infections, as was reported in a previous study (Pelaia et al, ). The underlying mechanism might be due to un‐disrupted interferon production in children with adequate asthma control compared with decreased interferon production in those with poor asthma control (Edwards et al, ; Sykes et al, ). Interferon is a major cytokine that regulates lung inflammation and protects lungs from infections.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show deficient local innate antiviral immune responses, as well as upregulated pro-T2 response with increased production of Th2 cytokines, in the setting of respiratory viral infections. In addition, recent evidence suggests that this susceptibility to viruses in asthmatics may be secondary to a defect in innate immunity (interferon signaling pathways) [40]. AECs in these patients demonstrate deficient type I and type III interferon (IFN) production in response to viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Rhinovirus-C is dependent on host epithelial CDHR3 as a receptor for cell entry thereby decreasing tight junctions in an already tenuous epithelial barrier. These observations, taken together, imply a mechanistic link between this host genomic variation and asthma risk [40]. …”
Section: Introductionmentioning
confidence: 99%
“…This defective antiviral response was more pronounced in a subgroup of patients prone to viral re‐infection at steady state. These findings need to be confirmed by other studies further determining the characteristics of patients more prone to develop virus‐induced severe exacerbation and disease progression . Indeed, long‐term consequences are unknown, and to our knowledge, no study has yet assessed the relationship between inflammatory and antiviral response during severe exacerbations and future asthma outcomes.…”
Section: Population Characteristics According To 1‐year Outcomesmentioning
confidence: 99%
“…Poor control and history of exacerbation are known risk factors of future exacerbation . Fielding et al have recently confirmed the link between altered lung function and poor asthma control and risk of exacerbation .…”
Section: Population Characteristics According To 1‐year Outcomesmentioning
confidence: 99%